Prevalence of streptococcus pneumoniae in elderly with pneumonia: A meta-analysis and systematic review in Asia - Soenarti, Sri; Wijaya, Yannita; Pratama, Adhya; Nugraha, Aditya; Seto, Agnes; Fathoni, Alfan; Sekarani, Ayu; Utama, Gede; Juhandana, Madya; Ardiyanti, Putri; Utomo, Vidi; Safira, Zahra; Sholichah, Zuhrotus; Santoso, Dimas (Deka in Medicine, 2024)
BACKGROUND: There is currently insufficient study focusing on comprehensive studies that thoroughly assess the prevalence of Streptococcus pneumoniae specifically among elderly patients with pneumonia in Asia. OBJECTIVE: To analyze the prevalence of Streptococcus pneumoniae as a causative factor of pneumonia among elderly populations in Asian countries. METHODS: This meta-analysis was designed to systematically collect data from PubMed, Scopus, and Embase within the timeframe of January to February 2024. The study focused on gathering prevalence data of Streptococcus pneumoniae among elderly patients diagnosed with pneumonia in Asian countries. Statistical analysis employed a single-arm meta-analysis methodology to consolidate and evaluate the cumulative prevalence of Streptococcus pneumoniae in this specific population group. RESULTS: The total sample included in our study comprised 15 articles. Through our analysis, we found that the cumulative prevalence of Streptococcus pneumoniae among elderly patients diagnosed with pneumonia in Asia was 9% (Event rate: 0.09; 95% CI: 0.06, 0.12; Egger's test: p = 0.7047; p Heterogeneity < 0.0001; p < 0.0001). CONCLUSION: Streptococcus pneumoniae remains a plausible causative agent of pneumonia in elderly Asian populations.